Extremity Joint Range of Motion Exercise on Intradialytic Blood Pressure Control in Hemodialysis Patients - Maula, Dedeh Riayatul; Rumahorbo, Hotma; Mauliku, Novi Elvinawaty; Suryati, Yayat; Murtiningsih, Murtiningsih (Indonesian Journal of Global Health Research, 2024)
Changes in blood pressure during hemodialysis is an important point that must be a concern. The occurrence of hypotension and intradialytic hypertension can have an impact on reducing the adequacy of dialysis, decreasing kidney function, and can even affect the patient's quality of life. Among the non-pharmacological interventions that are considered safe and effective in the management of intradialytic blood pressure control are intradialytic exercises, one of which is range of motion exercises for the extremities. To determine the effect of extremity joint range of motion exercises on intradialytic blood pressure control in hemodialysis patients. This research used a quasi-experimental pre-test and post-test control group design using cluster sampling with a purposive sampling technique with a sample size of 46 respondents (23 intervention and 23 control group respondents) with Wilcoxon test data analysis. in the intervention group the average systolic blood pressure before and after intradialytic exercise was -6.42mmHg, the diastolic blood pressure difference was -2.38mmHg with p value of systolic and diastolic blood pressure p=<0.05, In the control group systolic blood pressure p= 0.024 with a difference of 2.4, independent t test results mean systolic blood pressure 2.88mmHg and diastolic blood pressure mean 1.12mmHg with p value both P>0.05. Extremity joint range of motion exercises can affect blood pressure in the intervention group.